Clinical findings in patellofemoral osteoarthritis compared to individually-matched controls: a pilot study. Issue 1 (10th December 2020) - Macri, Erin M; Crossley, Kay M; Hart, Harvi F; d'Entremont, Agnes G; Forster, Bruce B; Ratzlaff, Charles R; Wilson, David R; Khan, Karim M
Abstract : Objective: To explore clinical characteristics in individuals with patellofemoral osteoarthritis (PFOA) compared to individually-matched asymptomatic controls. We also explored associations between functional performance and patient-reported symptoms with patellofemoral alignment. Methods: We assessed 15 individuals with PFOA and 15 individually-matched asymptomatic controls. In addition to physical examination and patient-reported questionnaires, we evaluated functional performance, lower extremity strength and range of motion, and patellar alignment (using MRI). We analysed group differences with Wilcoxon's matched-pairs signed rank tests, and within-group associations with Spearman's rank correlations. Results: We included 24 (80%) women with median (IQR) age of 56 (9) years and BMI of 22.8 (5.9) kg/m 2 . Individuals with PFOA reported lower quality of life (8/100 points lower EQ-5D-5L, p=0.02), and performed worse on two functional tests: repeated one-leg rises (median 16 fewer rises, p=0.04) and timed stair climb (1.2 s slower, p=0.03). There were no differences in strength tests performed or range of motion. Patellar proximal translation correlated with worse functional performance and worse patient-reported pain, function and self-efficacy, while lateral translation and lateral tilt correlated with worse knee-related quality of life (Spearman's r ranging from 0.5 to 0.7). Conclusion: Functional performance was worse in individuals with PFOA, despite those individuals having no significant differences on lower extremity strength testing. Patellofemoral alignment was associated with worse functional performance as well as worse patient-reported outcomes, and it may represent one mechanism underpinning PFOA-related symptoms.